The fungal metabolite eugenitin as additive for Aspergillus niveus glucoamylase activation - Andrioli, Willian J.; Silva, Tony M.; da Silva, Vinícius B.; Damásio, André R.L.; Maller, Alexandre; Conti, Raphael; Jorge, João A.; Araújo, Janete M.; Silva, Carlos H.T.P.; Pupo, Mônica T.; Polizeli, Maria L.T.M.; Bastos, Jairo K. (Journal of molecular catalysis. B, Enzymatic, 2012)
[Display omitted] ► We evaluated the biological activity of eugenitin as additive for glucoamylase. ► The compound increases the glucoamylase activity in twofold at 5 mM in different substrates and slightly affected the thermal stability and kinetics parameters. ► Molecular docking simulations revealed a possible binding mode of eugenitin with its molecular target. ► Endophytic microorganisms are a promising source of bioactive molecules. Endophytic microorganisms live inside tissues of host plants apparently do not causing warning to them, and are a promising source of bioactive molecules as antimicrobial and antitumoral drugs. In this work, we report the isolation of eugenitin from cultures of the endophyte Mycoleptodiscus indicus and its potential as additive for Aspergillus niveus glucoamylase activation. The glucoamylase hydrolytic activity increased twofold using 5 mM of eugenitin and this activation could be explained by the binding mode of eugenitin with the three-dimensional structure of glucoamylase. The in silico prediction of ligand binding sites revealed at least 9 possible interaction sites able to accommodate eugenitin on glucoamylase from Hypocrea jecorina. Besides, we evaluated the effect of pH and temperature on activity and stability, as well as in the hydrolysis of different substrates and kinetic parameters either in presence or absence of eugenitin. The results displayed by eugenitin as additive to glucoamylase activation are promising and provide novel perspectives for applications of fungal metabolites.